The Macroeconomic Factors Impact on Liquidity Risk: The Albanian Banking System Case - Madhi, Doris (European Journal of Economics and Business Studies, 2017)
Over the last five years, the Albanian banking system has experienced a deceleration on its activity, considering the recent financial crisis effects. The financial crisis did not propagate direct effects on the Albanian financial system, but indirect effects were visible based on the general slowdown of the foreign markets and public loss of confidence towards the banking system. Also, the foreign remittances decrease and the liquidity shortage of the public played an important role on the capacity to meet the payment obligations (especially on loans). During 2009, the Albanian Central Bank issued a new regulation on liquidity risk evaluation, monitoring and management. The main objective of the regulation was the determination of the minimal evaluation standards of liquidity risk and its effective management by all banks operating on the Albanian territory. The liquidity risk evaluation and monitoring, as suggested also by the literature, does not depend only on internal financial indexes of banks, but it finds its basis also on broader indexes such as macroeconomic indexes. This analysis is effectuated on the impact and importance these factors have on liquidity risk, considering the banking system composed by 13 banks over a period of five years.
Keywords: Albanian banking system, liquidity, liquidity risk, macroeconomic factors.